Spectral Geometry of Partial Differential Operators - Ruzhansky, Michael (Taylor & Francis, 2020)
Access; Differential; Durvudkhan; Geometry; Makhmud; Michael; OA; Open; Operators; Partial; Ruzhansky; Sadybekov; Spectral; Suragan